The mediating effect of community identity and the moderating effect of social comparison in the relationship between residential mobility and sense of meaning in life - Weifang, Song; Majie, Duan; Na, Zhao (Frontiers in Psychology, 2025)
IntroductionNumerous studies have documented the adverse effects of residential mobility; however, its relationship with the sense of meaning in life remains underexplored. This study examines the mechanisms by which residential mobility influences the subjective sense of meaning in life, focusing on the mediating role of community identity and the moderating role of social comparison.MethodsWe used the platform “Creator of Data and Model” to conduct an online survey. The sample of adult participants recruited were aged <35 years (85.0%).ResultsThe results revealed that residential mobility negatively predicts a sense of meaning in life, particularly through reduced community identity. Social comparison moderated these effects, with high social comparison tendencies exacerbating negative outcomes in specific dimensions.DiscussionThese findings advance our understanding of the psychological consequences of residential mobility and provide practical insights into supporting the well-being of mobile populations.ConclusionEnhancing community identity can mitigate the adverse effects of mobility, whereas tailored interventions for socially comparable individuals may improve their well-being.